2022
DOI: 10.1002/bit.28015
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a newly discovered microRNA in Chinese hamster ovary cells leads to upregulation of N‐glycolylneuraminic acid sialylation on monoclonal antibodies

Abstract: Chinese hamster ovary (CHO) cells are known not to express appreciable levels of the sialic acid residue N-glycolylneuraminic acid (NGNA) on monoclonal antibodies. However, we actually have identified a recombinant CHO cell line expressing an IgG with unusually high levels of NGNA sialylation (>30%). Comprehensive multi-OMICs based experimental analyses unraveled the root cause of this atypical sialylation: (1) expression of the cytidine monophosphate-N-acetylneuraminic acid hydroxylase (CMAH) gene was spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…An interesting observation related to the sialylation in CHO cells was reported by Fischer et al [65]. CHO cells are known to express a scarce amount of N-glycolylneuraminic acid (NGNA) compared to other nonhuman mammalian cell lines, such as mouse myeloma NSO and SP2/0 cell lines [66].…”
Section: Glycosylationmentioning
confidence: 91%
See 1 more Smart Citation
“…An interesting observation related to the sialylation in CHO cells was reported by Fischer et al [65]. CHO cells are known to express a scarce amount of N-glycolylneuraminic acid (NGNA) compared to other nonhuman mammalian cell lines, such as mouse myeloma NSO and SP2/0 cell lines [66].…”
Section: Glycosylationmentioning
confidence: 91%
“…The presence of the Cmah gene in CHO cells was confirmed [8], but the reason for its low expression is not known. An observation of unusually high levels of NGNA in one of the mAb-producing CHO cell lines revealed that the loss of the small non-coding RNA (cgr-miR-111) was responsible for the upregulation of the Cmah gene, resulting in increased NGNA levels [65].…”
Section: Glycosylationmentioning
confidence: 99%
“…The genomic CMAH gene locus was modified to produce a catalytically inactive version to examine the hypothesis that the model cell's enhanced protein NGNA sialylation is caused by the CMAH protein. The generated cell lines with a validated genomic knocking out of CMAH no longer had sialylation of the surface glycoprotein NGNA (Fischer et al, 2022). The majority of therapeutic recombinant glycoproteins with human‐like glycosylation are produced by mammalian hosts using CHO cells.…”
Section: Crispr‐cas9‐mediated Gene Ko For Cell Line Engineeringmentioning
confidence: 99%
“…Fischer et al showed that in CHO cells, a single point mutation in the promoter region of the cgr-miR-111 host gene sidekick cell adhesion molecule 1 (SDK1) caused deletion of miR-111. The resulting silencing of SDK1 and miR-111 leads to deregulation of (CMP)-N-acetylneuraminic acid hydroxylase (CMAH) expression and ultimately to increased N-glycolylneuraminic acid (NGNA) sialylation of recombinant mAb ( Fischer et al, 2021 ). At present, studies on the effects of miRNA on recombinant protein glycosylation in CHO cells are scarce and need to be further explored.…”
Section: Effect Of Mirna On the Production Of Recombinant Proteinmentioning
confidence: 99%